Development of Student Worksheets to Improve Students’ Science Literacy Skills on the Topic of Insects - Resti Pitafalah; Epa Paujiah; Tri Wahyu Agustina (FKIP - Universitas Riau, 2026)
The study aimed to develop science literacy-based Student Worksheets (LKPD) on the topic of insects. This Research and Development (R&D) study employed the 3D model, consisting of the define, design, and develop phases. The study participants included subject matter experts, pedagogical experts, and biology teachers who served as product validators. A pilot test was conducted on 41 students at a high school in Bandung Regency, West Java. Data analysis showed that the Student Worksheets (LKPD) had a high level of feasibility based on validation by subject matter experts (77,3%), pedagogical experts (85,3%), and biology teachers (95%), thus the LKPD was deemed highly suitable for use. The research instrument used was a validation sheet to assess the suitability of the science literacy-based LKPD. The results of the limited pilot test showed an increase in students’ science literacy skills with a score of 0,44, falling into the moderate category. The science literacy-based LKPD on the topic of Insects can be used as teaching material to improve science literacy.